Finite Element modelling of tunnelling-induced displacements on framed structures. (October 2018) - Boldini, Daniela; Losacco, Nunzio; Bertolin, Sara; Amorosi, Angelo
Highlights: This paper deals with the response to tunnelling of reinforced concrete framed structures. The study consists of a set of parametric numerical analyses. The foundations and the structural members of the building are modelled in detail. The structural stiffness reduces the differential settlements and the horizontal displacements. The deflection ratio in hogging increases as the number of floors becomes larger. Abstract: The construction of tunnels in urban areas inevitably entails the interaction with existing structures. While the effect of tunnel excavation on masonry structures has been thoroughly studied, the response of framed buildings has not been widely investigated in the past. In this paper, a parametric study of the response to tunnelling of reinforced concrete framed structures founded on strip footings is carried out using the Finite Element method. The foundations and the structural members of the building are modelled with a sufficient detail and a realistic contact law is employed to simulate the interaction between the foundation and the adjacent soil. Results are summarised in terms of deflection ratios and modification factors for horizontal strains. It is shown that the structural stiffness, mainly provided by the foundation, on average reduces the differential settlements and the horizontal displacements of the frame as compared to greenfield conditions. However, in contrast with what discussed in previously published papers, while the deflection ratio in sagging reduces as the number of floors becomes larger, it increases in hogging, which always occurs at the ends of the foundation. This evidence appears to be related to the non-uniform contact pressure at the soil-foundation interface and to the peculiar load distribution associated to the frame geometry.